Silencing susceptibility genes in potato hinders primary infection with Phytophthora infestans at different stages. Issue 1 (19th January 2022) - Sun, Kaile; Schipper, Danny; Jacobsen, Evert; Visser, Richard G F; Govers, Francine; Bouwmeester, Klaas; Bai, Yuling
Abstract: Most potato cultivars are susceptible to late blight disease caused by the oomycete pathogen Phytophthora infestans . Here we report that the genetic loss of host susceptibility is a new source of resistance to prevent or diminish pathogen infection. Previously, we showed that RNAi-mediated silencing of the potato susceptibility ( S ) genes StDND1, StDMR1, and StDMR6 leads to increased late blight resistance. The mechanisms underlying this S -gene-mediated resistance have thus far not been identified. In this study, we examined the infection process of P. infestans in StDND1 -, StDMR1 -, and StDMR6- silenced potato lines. Microscopic analysis showed that penetration of P. infestans spores was hampered in StDND1 -silenced plants. In StDMR1- and StDMR6- silenced plants, P. infestans infection was arrested at a primary infection stage by enhanced cell death responses . Histochemical staining revealed that StDMR1- and StDMR6- silenced plants display elevated ROS levels in cells at the infection sites. Resistance in StDND1 -silenced plants, however, seems not to rely on a cell death response as ROS accumulation was found to be absent at most inoculated sites. Quantitative analysis of marker gene expression suggests that the increased resistance observed in StDND1 - and StDMR6 -silenced plants relies on an early onset of salicylic acid- and ethylene-mediated signaling pathways. Resistance mediated by silencing StDMR1 was found to be correlated with the early induction of salicylic acid-mediated signaling. These data provide evidence that different defense mechanisms are involved in late blight resistance mediated by functional impairment of different potato S -genes.